Characterization of two cotton cDNAs encoding trans-2-enoyl-CoA reductase reveals a putative novel NADPH-binding motif - Song, Wen-Qiang (Journal of experimental botany, 2009)
Very long chain fatty acids are important components of plant lipids, suberins, and cuticular waxes. Trans-2-enoyl-CoA reductase (ECR) catalyses the fourth reaction of fatty acid elongation, which is NADPH dependent. In the present study, the expression of two cotton ECR (GhECR) genes revealed by quantitative RT-PCR analysis was up-regulated during cotton fibre elongation. GhECR1 and 2 each contain open reading frames of 933 bp in length, both encoding proteins consisting of 310 amino acid residues. GhECRs show 32% identity to Saccharomyces cerevisiae Tsc13p at the deduced amino acid level, and the GhECR genes were able to restore the viability of the S. cerevisiae haploid tsc13-deletion strain. A putative non-classical NADPH-binding site in GhECR was predicted by an empirical approach. Site-directed mutagenesis in combination with gas chromatography-mass spectrometry analysis suggests that G(5X)IPXG presents a putative novel NADPH-binding motif of the plant ECR family. The data suggest that both GhECR genes encode functional enzymes harbouring non-classical NADPH-binding sites at their C-termini, and are involved in fatty acid elongation during cotton fibre development